Pengaruh Daya Tarik Pesan Iklan Layanan Masyarakat di Youtube dan Tingkat Pengetahuan Masyarakat Terhadap Keputusan Menggunakan Vaksin Measles dan Rubella (Mr) pada Anak (Studi Eksplanatif pada Subscribe Iklan Layanan Masyarakat Vaksin Measles dan Ru - Ilona Vicenovie Oisina; Ivonne Ruth Vitamaya Oishi (KOMUNIDA : Media Komunikasi dan Dakwah, 2019)
Social media is the target of advertisers to advertise various products andservices. Similarly, public service advertisements use social media to advertise.The selected social media varies depending on needs. Public serviceadvertisements about MR vaccines are available on various social media, one of which is on Youtube, with many versions. In this study took public serviceadvertisements about the long version of the MR vaccine. It is expected that publicservice advertisements can provide knowledge for users to know that MR vaccinesare important for children's development, and not contrary to any religion. Thisresearch uses the theory of Computer Mediated Communication. The paradigmused positivism with quantitative approaches, the nature of explanatory researchand survey research methods. The population is to subscribe to 2146 publicservice advertisements as of January 2018 with a sample of 96 respondents takenusing purposive sampling. The results obtained from the relationship of theattractiveness of public service advertisements and the level of knowledge withuse decisions are 0.494. F count test> F table is 15,768> 3,099, it can beconcluded that there is a simultan eous influence of the attraction of MR vaccinepublic service ads and the level of knowledge on the decision to use MR vaccine.